Infusing Argumentation Activity on The Anticipation Guides Strategy to Improve The Reading Literacy: A Study on The Topic of Heat and Temperature - Siswanto Siswanto; Nuryunita Dewantari; Bambang Subali; Muhammad Daniel Fahmi R; Surya Gumilar (Jurnal Pendidikan Fisika Indonesia, 2026)
Reading literacy is a basic ability to master conceptual understanding and high-order thinking skills. The latest PISA results show that Indonesians are at a low level of reading literacy achievement. This research was conducted to test the effectiveness of implementing the anticipation guides strategy, which is integrated with argumentation activities in improving students' reading literacy (literal, inferential, and critical indicators). A non-equivalent pre-test post-test control group was carried out. In the experimental class, the anticipation guide is implemented by inserting argumentation activities. The traditional reading strategy used in the control class was where students were asked to read the textbook directly. The findings show that reading literacy was increased significantly in the experimental class. Students who learned through Anticipation Guides integrated with argumentation activities demonstrated a greater improvement in reading literacy compared to those who experienced traditional reading activities. The integration of argumentation activities in Anticipation Guides proved to be effective in stimulating the activation of prior knowledge, strengthening inferential abilities, and fostering critical evaluation of reading texts. This research is useful in providing both practical and theoretical contributions in the development of science learning that trains students' reading literacy by inserting an argumentation activity on reading.